2014
DOI: 10.5455/gmj-30-45779
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of exclusive breastfeeding among antenatal attendees in Uyo, Southern Nigeria

Abstract: The aim was to assess the knowledge and practice of exclusive breastfeeding among women receiving antenatal care in the teaching hospital. Semi-structured questionnaires were administered to two hundred women in the antenatal clinic. Majority of the respondents (69.5%) were between 25-34 years of age, 57.0% were multiparous and 67.7% had attained tertiary level education. Eighty-four women (42.0%) were able to define exclusive breastfeeding correctly while just 7.0% of the respondents knew the ten steps to suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
8
8
1
Order By: Relevance
“…The urban slum population constitute one of the fastest growing sections of the society with millions of babies being born annually. Breast feeding practices of children among urban slum dwellers is considered poor leading to various conditions of ill health and malnutrition Our study revealed that only 47.8% of the respondent had the correct knowledge regarding EBF which was almost similar to study done by Ouchi et al 12 where (31%) mothers had adequate knowledge of exclusive breastfeeding and in a study done by Abasiattai et al 13 showed (42.0%) of antenatal attendees were able to define exclusive breastfeeding correctly. However, the figure obtained in this study is low when compared to the study done by Oluwatosin et al 14 19 showed 80% of the mothers had the knowledge to initiate breastfeeding within one hour of delivery.…”
Section: Discussionsupporting
confidence: 76%
“…The urban slum population constitute one of the fastest growing sections of the society with millions of babies being born annually. Breast feeding practices of children among urban slum dwellers is considered poor leading to various conditions of ill health and malnutrition Our study revealed that only 47.8% of the respondent had the correct knowledge regarding EBF which was almost similar to study done by Ouchi et al 12 where (31%) mothers had adequate knowledge of exclusive breastfeeding and in a study done by Abasiattai et al 13 showed (42.0%) of antenatal attendees were able to define exclusive breastfeeding correctly. However, the figure obtained in this study is low when compared to the study done by Oluwatosin et al 14 19 showed 80% of the mothers had the knowledge to initiate breastfeeding within one hour of delivery.…”
Section: Discussionsupporting
confidence: 76%
“…The findings further indicate that the health facility or place of delivery was the first port of call in receiving information on breastfeeding. This is therefore consistent with the findings of a study conducted in Southern Nigeria where mothers reported often obtaining EBF information when they attended antenatal clinics in health facilities (30).…”
Section: Discussionsupporting
confidence: 91%
“…The findings indicate that the health facility or place of delivery was the first point of call in receiving information on breastfeeding. This is therefore consistent with the findings of a study conducted in Southern Nigeria where mothers reported often obtaining EBF information when they attended antenatal clinics in health facilities (30). On a whole, participants knew EBF as a standard practice, which makes no room for alternative feeding for babies within the specified six-month period…”
Section: Discussionsupporting
confidence: 88%